How Founder Personal Branding Strengthens Corporate Reputation: The Case of Nurhayati Subakat and Paragon Corp - Felixza Faimica Arsetyafna; Rosalia Anindita Ningrum; Widya Dwi Safitri; Pramudya Ibnu Subrata (The Indonesian Institute of Science and Technology Research, 2026)
The growing demand for authenticity in corporate communication has shifted public relations from organization-centered messaging toward founder-driven narratives that emphasize personal values as strategic organizational assets. This study investigates how founder personal branding strengthens corporate reputation through the alignment of individual and organizational values, using Paragon Corp and its founder, Nurhayati Subakat, as a qualitative case study. Situated within the highly competitive and value-oriented halal cosmetics industry, the research examines how the founder’s values of spirituality, humility, integrity, and care are embedded in the company’s organizational culture and stakeholder engagement practices. The study adopts a qualitative case study design supported by document analysis, public communication materials, and secondary data. The analysis is guided by the Values-Driven Persona framework and Person–Organization Fit (P–O Fit) theory to explain how founder identity is transformed into organizational legitimacy and reputational capital. The findings demonstrate that the alignment between Nurhayati Subakat’s personal values and the “Paragon Way” corporate culture creates a coherent organizational identity that enhances stakeholder trust, brand authenticity, and corporate credibility. This value alignment also functions as a reputational safeguard by reducing stakeholder skepticism and fostering long-term emotional commitment, particularly within collectivist cultural contexts. The study contributes to the literature on founder-led branding by proposing value alignment as a fundamental mechanism linking founder personal branding with sustainable corporate reputation. Future research should validate this conceptual framework across different industries and cultural settings using quantitative and comparative approaches.